Food‐related salience processing in healthy subjects during word recognition: Fronto‐parietal network activation as revealed by independent component analysis - Safi, Annette (Brain Behav, 2017)
BACKGROUND: The study aimed to isolate and localize mutually independent cognitive processes evoked during a word recognition task involving food‐related and food‐neutral words using independent component analysis (ICA) for continuously recorded EEG data. Recognition memory (old/new effect) involves cognitive subcomponents—familiarity and recollection—which may be temporally and spatially dissociated in the brain. Food words may evoke additional attentional salience which may interact with the old/new effect. METHODS: Sixteen satiated female participants undertook a word recognition task consisting of an encoding phase (learning of presented words, 40 food‐related and 40 food neutral) and a test phase (recognition of previously learned words and new words). Simultaneously recorded 64‐channel EEG data were decomposed into mutually independent components using the Infomax algorithm in EEGLAB. The components were localized using single dipole fitting using a four‐shell BESA head model. The resulting (nonartefactual) components with <15% residual variance were clustered across subjects using the kmeans algorithm resulting in five meaningful clusters localized to fronto‐parietal regions. Repeated‐measures anova was employed to test main effects (old/new and food relevance) and their interaction on cluster time courses. RESULTS: Early task‐relevant old/new effects were localized to the medial frontal gyrus (MFG) and later old/new effects to the right parietal regions (precuneus). Food‐related (nontask‐relevant) salience effects were localized to bilateral parietal regions (left precuneus and right postcentral gyrus). Food‐related salience interacted with task relevance, the old/new effect in MFG being significant only for food‐neutral words highlighting central the role of MFG as the converging site of endogenous and exogenous salience inputs. CONCLUSION: Our results indicate ICA to be a valid technique to decompose complex neurophysiological signals involving multiple cognitive processes and implicate the fronto‐parietal network as an important attentional network for processing salience and task demands.